2021
DOI: 10.1039/d0ta11311e
|View full text |Cite
|
Sign up to set email alerts
|

Modifying an ultrathin insulating layer to suppress lithium dendrite formation within garnet solid electrolytes

Abstract: The ultrathin insulating LiF coating with controllable thickness is proposed as an interfacial layer for garnet electrolytes to inhibit the formation of Li dendrites, and promote uniform Li plating/stripping.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
39
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 47 publications
(39 citation statements)
references
References 53 publications
0
39
0
Order By: Relevance
“…Crystalline LLZO thin films were normally annealed in the temperature range of 600–1000 °C, mostly exhibiting a conductivity of ∼10 –6 S cm –1 at room temperature . Very recently, high-conducting cubic LLZO-based thin films with a room-temperature conductivity of 10 –5 to 10 –4 S cm –1 was obtained by the pulsed laser deposition and radio frequency sputtering techniques. , Nevertheless, crystalline LLZO thin films contain grain boundaries which may retard the Li-ion transport and incur the penetration of Li dendrites. In contrast, amorphous LLZO thin films have advantages of grain boundary-free and isotropic features, which can naturally suppress the formation and penetration of Li dendrites across the electrodes to cause a short circuit. In addition, the processing temperature (300–600 °C) and time (normally several minutes) for amorphous LLZO films are also much lower and lesser than that for crystalline films, demonstrating better adaptability for the large-scale production of ASSLBs at low cost.…”
Section: Introductionmentioning
confidence: 99%
“…Crystalline LLZO thin films were normally annealed in the temperature range of 600–1000 °C, mostly exhibiting a conductivity of ∼10 –6 S cm –1 at room temperature . Very recently, high-conducting cubic LLZO-based thin films with a room-temperature conductivity of 10 –5 to 10 –4 S cm –1 was obtained by the pulsed laser deposition and radio frequency sputtering techniques. , Nevertheless, crystalline LLZO thin films contain grain boundaries which may retard the Li-ion transport and incur the penetration of Li dendrites. In contrast, amorphous LLZO thin films have advantages of grain boundary-free and isotropic features, which can naturally suppress the formation and penetration of Li dendrites across the electrodes to cause a short circuit. In addition, the processing temperature (300–600 °C) and time (normally several minutes) for amorphous LLZO films are also much lower and lesser than that for crystalline films, demonstrating better adaptability for the large-scale production of ASSLBs at low cost.…”
Section: Introductionmentioning
confidence: 99%
“…According to the x-ray diffraction (XRD) analysis in fig. S1, the as-prepared LLZTO was successfully synthesized as a cubic phase garnet ( 31 ) without any noticeable impurities such as Li 2 CO 3 . For reference, the ionic and electronic conductivities of the pristine LLZTO were measured by the electrochemical impedance spectroscopy (EIS) spectra and direct-current (DC) polarization curves and were observed to be 0.45 mS cm −1 and 5.00 × 10 −9 S cm −1 at room temperature, respectively, consistent with previously reported values for garnet electrolytes (fig.…”
Section: Resultsmentioning
confidence: 99%
“…It was further demonstrated that the electronic conductivity of garnet-type electrolytes can surge when exposed to high applied potentials or temperature, showing the electric breakdown properties at certain threshold voltages ( 30 ) and temperature, implying the risk of electrical leakage through the solid electrolyte at fast charging/discharging or high-temperature operating conditions. The presence of the electron-conducting pathways inside the solid electrolyte suggests the feasibility of the lithium metal nucleation and growth preferentially along these paths, consequently incurring a risk of short circuit ( 31 , 32 ).…”
Section: Introductionmentioning
confidence: 99%
“…5,7,9,28,29 In addition to optimising the Li-ion conductivity of lithium-rich garnets via cationic doping, considerable attention has been focused on overcoming the high interfacial resistance between the electrolyte and electrodes, as well as trying to eliminate dendrite inltration through the electrolyte. [30][31][32][33][34][35][36][37][38] It has been reported that the application of coatings to the garnet pellets (and consequently lithium alloying with the coating at the interface) and hybrid polymer-garnet electrolyte composite systems can mitigate these problems to a degree. [39][40][41][42][43][44][45][46][47][48][49] Short circuiting behaviour in the garnet system was also recently reported to be reversible, which can be healed by a low current density electrochemical process.…”
Section: Introductionmentioning
confidence: 99%